2015
DOI: 10.1039/c5nr00013k
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-derived nitrogen self-doped porous carbon as effective metal-free catalysts for oxygen reduction reaction

Abstract: Biomass-derived nitrogen self-doped porous carbon was synthesized by a facile procedure based on simple pyrolysis of water hyacinth (eichhornia crassipes) at controlled temperatures (600-800 °C) with ZnCl2 as an activation reagent. The obtained porous carbon exhibited a BET surface area up to 950.6 m(2) g(-1), and various forms of nitrogen (pyridinic, pyrrolic and graphitic) were found to be incorporated into the carbon molecular skeleton. Electrochemical measurements showed that the nitrogen self-doped carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
175
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(181 citation statements)
references
References 47 publications
6
175
0
Order By: Relevance
“…For further study, we compared the ORR catalytic property of N-BC@G-900 with other catalysts [13,14,17,21,35,36,38], as displayed in Table S1 (online). Our results are comparable with those of the best N-doped carbon catalysts reported to date in terms of E ORR , half-wave potential, average electron transfer number (n) and limited current density, but the BET surface area of the N-BC@G-900 catalyst is much lower than that of numerous nitrogen-doped carbon catalysts [16,33,34]. In fact, the major reason for the electrocatalytic activity enhancement is the density of surface active sites rather than the total surface area, although the significance of the BET specific surface area cannot be ruled out totally [31].…”
Section: Electrocatalytic Performance For Oxygen Reductionsupporting
confidence: 92%
See 1 more Smart Citation
“…For further study, we compared the ORR catalytic property of N-BC@G-900 with other catalysts [13,14,17,21,35,36,38], as displayed in Table S1 (online). Our results are comparable with those of the best N-doped carbon catalysts reported to date in terms of E ORR , half-wave potential, average electron transfer number (n) and limited current density, but the BET surface area of the N-BC@G-900 catalyst is much lower than that of numerous nitrogen-doped carbon catalysts [16,33,34]. In fact, the major reason for the electrocatalytic activity enhancement is the density of surface active sites rather than the total surface area, although the significance of the BET specific surface area cannot be ruled out totally [31].…”
Section: Electrocatalytic Performance For Oxygen Reductionsupporting
confidence: 92%
“…One widely used strategy for synthesis of the doped carbon catalysts is to use natural biomass as a nitrogen source of active centers or a direct precursor [15,16]. Several typical biomass precursors, previously reported in the literatures, include soybean [17], pig bone [18], silk fibroin [19], nori [20], blood protein [21], and hemoglobin [22].…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al [15] extensively studied the solubility of cellulose in metal chloride hydrate melts. In fact, it was recently shown that cheap and abundant biomass can also be used for the synthesis of structurally very similar materials [22][23][24][25][26]. In other work, LiCl/KCl, cesium acetate or Na 2 CO 3 /K 2 CO 3 melts were used as flux to obtain oligographene, carbon gels or active carbon [27][28][29].…”
Section: Inorganic Salt Melts As Porogen and Solventmentioning
confidence: 99%
“…Porous materials have received a great deal of attention since it poses the high specific surface area, diverse porous structure, stability in different chemical environments, and easy accessibility, [1] which can be used for gas adsorption or liquid separation, [2] catalysis, [3] electric, [4] and battery [5] fields. In addition to the porosity, the conductivity and hydrophilicity are major key factors for the case of electrochemical sensors or biosensors used in biochemical applications such as the detection of H 2 O 2 or methanol.…”
Section: Introductionmentioning
confidence: 99%